2019
DOI: 10.22598/pi-be/2019.13.1.57
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Social and Cultural Factors on Success of Trade Internationalization

Abstract: Trading companies that expand their operations beyond the national borders need to know the determinants or factors affecting the success of the internationalization strategy. Theoretical and practical research of the past twenty years has seen these factors as a set of economic, political, social, and cultural factors, which, ultimately, determine the choice of the specific market to operate on in the next period. In addition, research results in this field consider internationalization factors on two grounds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Their transfer requires a certain level of economic development, a flexible trade policy, but also an appropriate level of overall education of the population. Thus, some studies have shown difficulties in transferring supermarket technology to less developed countries (Ćuzović, Sokolov Mladenović & Ćuzović, 2019). Specifically, the supermarket technology is based on a constant and rich supply of energy, prepackaged products prepared for widespread use, on modern services and communication, but also on a wide and diversified offer of products and services.…”
Section: Theoretical Backgrounds Of Institutional Innovation In Tradementioning
confidence: 99%
“…Their transfer requires a certain level of economic development, a flexible trade policy, but also an appropriate level of overall education of the population. Thus, some studies have shown difficulties in transferring supermarket technology to less developed countries (Ćuzović, Sokolov Mladenović & Ćuzović, 2019). Specifically, the supermarket technology is based on a constant and rich supply of energy, prepackaged products prepared for widespread use, on modern services and communication, but also on a wide and diversified offer of products and services.…”
Section: Theoretical Backgrounds Of Institutional Innovation In Tradementioning
confidence: 99%